2016
DOI: 10.1111/aji.12498
|View full text |Cite
|
Sign up to set email alerts
|

Fyn Plays a Pivotal Role in Fetomaternal Tolerance Through Regulation of Th17 Cells

Abstract: Fyn is confirmed as a negative regulator in fetomaternal immune tolerance, through promoting Th17 cell expansion and proinflammatory factors expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…As reported, no matter whether in patients suffering from spontaneous abortion or LPS‐injected murine models, increased serum levels of IL‐17A, expansion of CD4 + IL17A + T cells in the peripheral blood and spleen and infiltration of Th17 cells into the maternal‐fetal interface are observed 48,49 . Our study also found the same results.…”
Section: Discussionsupporting
confidence: 90%
“…As reported, no matter whether in patients suffering from spontaneous abortion or LPS‐injected murine models, increased serum levels of IL‐17A, expansion of CD4 + IL17A + T cells in the peripheral blood and spleen and infiltration of Th17 cells into the maternal‐fetal interface are observed 48,49 . Our study also found the same results.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, the AMD1 protein was located in luminal and epithelial cells of bovine endometrium [43]. This window also harbors FYN associated with mouse oocyte maturation [44] and maternal-fetal immune tolerance in humans and mice [45], REV3L which contributes to genome stability during neoplastic transformation and progression in mice—targeted disruption of this gene results in lethality during midgestation [46, 47], and SLC16A10 which is differentially expressed in human placenta at mid-gestation, regulating embryonic development and growth [48]. Window 70-71Mb of BTA 17 was significant for both traits.…”
Section: Resultsmentioning
confidence: 99%
“…In a consistent manner, the functional enrichment analysis of hub genes in placental villi showed that the regulated genes were mainly related to the regulation of cell proliferation, angiogenesis, cell migration, and focal adhesion, which are important processes involved in placental and fetal development. Studies have demonstrated that FYN expression, which is elevated at the fetomaternal interface of abortion-prone mice and RPL patients, plays a role in the regulation of fetomaternal immune tolerance by encouraging the expansion of Th17 cells and the expression of proinflammatory factors (Khan et al, 2014;Liu et al, 2016). A FYN inhibitor overcomes the aberrant inflammatory state and embryo resorption caused by LPS (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%